Digital Development of Modest Wear Design Video Tutorials in Phase F of Fashion Design and Production at SMKN 1 Sarirejo - Yuniar, Mevita Nur Adma; Yuniati, Mita; Marniati, Marniati (Universitas Syiah Kuala, 2025)
This study aims to determine the development of digital modest wear design video tutorials in phase F of fashion design and production at SMKN 1 Sarirejo. This study uses the Research and Development (RD) method with the ADDIE development model consisting of five stages, namely analysis, design, development, implementation, and evaluation. The study was conducted at SMKN 1 Sarirejo in the odd semester of the 2025/2026 academic year with 23 research subjects of Vocational Competency 2 (KK2) subjects. Data were collected through validation of learning video media and product assessment. Data analysis was carried out by calculating the level of media feasibility and student learning outcomes. The findings in this study are the results of the feasibility of the video tutorial media achieved an average score of 4.62 from media experts with a very feasible category. Then from material experts obtained an average score of 4.88 with a very feasible category. The percentage of student learning outcomes completeness showed a very good category and received an assessment of 87.5% complete with 12.5% incomplete. It can be concluded that the existence of digital video tutorial learning media for modest wear design can influence the level of achievement of student learning outcomes.